The Content of Biologically Active Substances in Phytobiotics Used for Agricultural Animals and Poultry - Victorovna Ulrikh, Elena; Shamilovich Khaliullin, Rafik; Alexandrovna Ganieva, Irina; Aleksandrovna Izhmulkina, Ekaterina; Nikolayevich Arzjutov, Mikhail (International Journal of Engineering and Technology, 2018)
Medicinal plants are producers of many biologically active substances â€“ compounds that can influence biological processes in animals; such compounds include cardiac glycosides, saponins, sterols, carotenoids, polyphenols, alkaloids, vitamins, quinones, as well as substances with specific aroma, taste and color. Objects of theÂ research were the extracts of purple coneflower (Echinacea purpurea), maral root (Leuzea carthamoides), holy thistle (Silybum marianum) and marigold (Calendula officinalis) obtained by low-temperature water-ethanolic extraction followed by low-temperature vacuum drying of the extracts. The content of biologically active substances was determined in accordance with the standard methods of chemical analysis for phytobiotic substances. As shown by the results of the studies, phytobiotic substances contain ascorbic acid, polysaccharides, tannins, carotenoids, phytosterols, fructose and inulin. They also contain many flavonoids, which, presumably, efficiently alter the economic-useful qualities of agricultural animals and poultry. The phytobiotical feed additives may indirectly control the intestinal microflora, supporting the internal protective mechanisms of the animal organism. The use of phytobiotical feed additives in the diet of farm animals and poultry is rationally substantiated, and contributes to abandoning theÂ use of antibiotics in theÂ fodder. Â